Microenvironment Influence of a Novel Bioengineered Wound Product, APIS®: A Preliminary In Vitro Analysis of Inflammatory Marker and Growth Factor Secretion. (22nd March 2021) - Rodriguez, Isaac; Conti, Tricia; Bionda, Nina
Abstract : Objective . Preliminary biological activity assessment of a novel bioengineered wound product ( APIS®, SweetBio, Inc., Memphis, TN, USA ), a synthesis of gelatin, Manuka honey, and hydroxyapatite, with in vitro indications to protect, instill balance to, and progress the wound microenvironment. Approach . The biological activity the bioengineered wound product (BWP) elicits on human cells in vitro was assessed by evaluating matrix metalloproteinase- (MMP-) related proteins expressed by macrophages and secretion of growth factors in fibroblasts. Cells were cultured with no treatment, stimulated with lipopolysaccharides (LPS), or seeded directly on the BWP for 24 hours. An additional 72-hour time point for the BWP was assessed to determine if the BWP maintained its activity compared to itself at 24 hours. Cell culture supernatants were assayed to quantify secreted protein levels. Results . MMP-9 secretion from macrophages seeded on the BWP were nondetectable (P < 0.01 ), while a tissue inhibitor of MMP (TIMP-1) was detected. This decreased the overall MMP-9/TIMP-1 ratio secreted from macrophages seeded on the BWP compared to the controls. Additionally, the secretion of prohealing growth factors such as basic fibroblast growth factor (FGFb) and vascular endothelial growth factor (VEGF) was observed. Conclusion . Results from this preliminary in vitro evaluation suggest that the BWP has the potential to instill balance to the wound microenvironment by reducing the MMP-9/TIMP-1 ratio secretion from macrophages and progress previously stalled chronic wounds towards healing by triggering the release of growth factors from fibroblasts.